2018
DOI: 10.2147/ijgm.s125051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of plecanatide in the treatment of chronic idiopathic constipation

Abstract: Constipation is an important health burden that reduces the quality of life for countless millions of people. Symptom-centric therapeutics are often used to treat constipation due to unknown etiology, but in many cases, these drugs are either inadequate or have significant side effects. More recently, synthetic peptide agonists for epithelial guanylyl cyclase C (GC-C) have been developed which are effective at treating constipation in a sub-population of adult constipation patients. The first to market was lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In accordance with these findings, Boulete and others (Boulete et al, 2018) indicated that activation of GC-C signaling may be an attractive therapeutic approach to treat functional constipation disorders and inflammatory gastrointestinal conditions (Boulete et al, 2018). Recent studies reported that GC-C agonists plecanatide and linaclotide can be used in the treatment of chronic idiopathic constipation (Lembo et al, 2011;Islam et al, 2018). As we know, diarrhea is the most common manifestation of UC.…”
Section: Introductionmentioning
confidence: 69%
“…In accordance with these findings, Boulete and others (Boulete et al, 2018) indicated that activation of GC-C signaling may be an attractive therapeutic approach to treat functional constipation disorders and inflammatory gastrointestinal conditions (Boulete et al, 2018). Recent studies reported that GC-C agonists plecanatide and linaclotide can be used in the treatment of chronic idiopathic constipation (Lembo et al, 2011;Islam et al, 2018). As we know, diarrhea is the most common manifestation of UC.…”
Section: Introductionmentioning
confidence: 69%
“…Chronic idiopathic constipation is the most commonly diagnosed subtype of chronic constipation [ 9 , 10 ] and can be divided into normal-transit constipation, slow-transit constipation (STC), and DDs [ 4 ]. CIC is diagnosed when there are no identifiable physiological or biochemical etiologies of the symptom complex [ 10 ].…”
Section: Diagnosing Constipation In a Primary Care Settingmentioning
confidence: 99%
“…Chronic constipation may or may not have an identifiable cause; causes may be primary (related to intrinsic gastrointestinal structure and function) or secondary (related to systemic disease or medication) [ 1 , 9 ]. An identifiable cause of constipation is unknown in the largest subset of chronic constipation sufferers [ 10 ]. Primary constipation can be caused by functional colonic abnormalities or by defects in the process of defecation itself [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other causes of constipation include opioid use, which can result in the delay of colonic transit and reduction in intestinal motility and absorption, eventually resulting in constipation. Also, for chronic idiopathic constipation, the relatively unbalanced expression of cyclic guanosine monophosphate (cGMP) signaling components can potentially cause constipation; moreover, overexpression of PDE5 can also cause refractory constipation; it cannot be treated with linaclotide or plecanatide, but PDE5 inhibitors can provide treatment for this type of constipation …”
Section: Common Intestinal Diseasesmentioning
confidence: 99%
“…Therefore, InFroMs represent a novel nanoplatform that can be used for multimodal imaging of the intestine . Beyond that, other novel imaging strategies are adding new possibilities to the field of theranostics and molecular imaging …”
Section: Perspectivesmentioning
confidence: 99%